Pendampingan dan Pelayanan Posyandu Balita dengan Kreasi Es Krim Biofarmasi Eksplorasi Fitoaktif Curcuma Xanthorrhiza Melalui Teknik Krioadopsi Sebagai Makanan Pendamping Posyandu Kelurahan Karanganyar - Ilmiyatur Rosyidah; Galang Febriansyah; Nikmatul Hizah; M. Toriqul Firdausi; Roudlotul Fadiyah; Yulia Hidayatul Musyarofah (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
This community service aims to optimize the use of temulawak (Curcuma xanthorrhiza) which is abundant in Karanganyar Village, Pasuruan, through the innovation of making temulawak ice cream as a complementary food in Posyandu Toddler activities. Although temulawak is known to have various health benefits, its use in this community is still very minimal. This program began with a needs analysis conducted through interviews and observations, identifying challenges in utilizing local rhizome plants and the need for complementary food innovations. The results of this analysis encouraged the development of temulawak ice cream using cryoadoption techniques to maintain nutritional content and provide optimal health benefits. The community service method was carried out with a participatory approach involving residents of Karanganyar Village, Posyandu cadres, and village officials. This process includes education, training, and implementation of temulawak ice cream in Posyandu activities. Evaluations were carried out on the taste, texture, and children's interest in the ice cream. The evaluation results showed that 80% of respondents really liked the taste of temulawak ice cream, 70% considered the texture soft, and 90% showed high interest in this product. This program is expected to increase the utilization of local rhizome plants, introduce healthy food innovations, and strengthen community awareness and participation in health programs. Overall, this service shows success in optimally utilizing local potential and providing a positive impact on public health and community empowerment, with the hope that this innovation can be a model for the development of similar products in other areas